2017
DOI: 10.3892/ijo.2017.3880
|View full text |Cite
|
Sign up to set email alerts
|

UBE2C induces EMT through Wnt/β-catenin and PI3K/Akt signaling pathways by regulating phosphorylation levels of Aurora-A

Abstract: The ubiquitin-conjugating enzyme 2C (UBE2C) is the key component in the ubiquitin proteasome system (UPS) by partnering with the anaphase-promoting complex (APC/C). A high UBE2C protein expression level has been reported in various types of human tumors. However, little is known about the precise mechanism by which UBE2C expression is downregulated in gastric cancer. We found in MGC-803 and SGC-7901 gastric cancer cells UBE2C-deficient G2/M phase arrest in the cell cycle and subsequently decreased gastric aden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 40 publications
3
46
0
Order By: Relevance
“…41 In addition, UBE2C knockdown impeded EMT by repressing the phosphorylation of the hub oncogenic gene Aurora-A in gastric adenocarcinoma. 32 In this study, our data revealed that UBE2O could potentiate TGF-β1-induced EMT, leading to enhanced proliferation, motility and metastatic capacity in HNSCC cells. Interestingly, Zhang et al reported that UBE2O promoted the monoubiquitination of inhibitory Smad6 and therefore facilitated adipogenesis induced by BMP7; 10 these findings indicated that UBE2O could skew the balance of the Smad-dependent signaling pathways toward a stimulatory status via the inactivation of inhibitory Smads, including Smad6/7.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…41 In addition, UBE2C knockdown impeded EMT by repressing the phosphorylation of the hub oncogenic gene Aurora-A in gastric adenocarcinoma. 32 In this study, our data revealed that UBE2O could potentiate TGF-β1-induced EMT, leading to enhanced proliferation, motility and metastatic capacity in HNSCC cells. Interestingly, Zhang et al reported that UBE2O promoted the monoubiquitination of inhibitory Smad6 and therefore facilitated adipogenesis induced by BMP7; 10 these findings indicated that UBE2O could skew the balance of the Smad-dependent signaling pathways toward a stimulatory status via the inactivation of inhibitory Smads, including Smad6/7.…”
Section: Discussionmentioning
confidence: 52%
“…30,31 For instance, UBE2C is overexpressed in diverse human cancers and promotes malignant tumor progression through the activation of multiple oncogenic signaling pathways, including Wnt/β-catenin, Erk and PI3K/Akt pathways. [32][33][34] However, the function of UBE2O still remains unknown. UBE2O was first purified from rabbit reticulocytes and considered an E2 enzyme due to its specific and conserved ubiquitin-conjugating domain.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of CCNB1 ( Begnami et al, 2010 ) and TPX2 ( Tomii et al, 2017 ) have been demonstrated to be associated with poor survival in Gc. Further, UBE2C induced epithelial-mesenchymal transition (EMT) by regulating phosphorylation levels of AURKA ( Wang et al, 2017 ). Therefore, we hypothesized that AURKA was related to poor survival of GC.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that AURKA is involved in multiple mechanisms-associated with cancer initiation [51]. AURKA overexpression was also suggested to increase the expression of MMP-2, MMP-7, MMP-9, leading to tumor metastasis by degrading extracellular matrix proteins [52][53][54]. Zhong et al [55] identified AURKA as potential therapeutic targets in glioblastoma-bearing rats.…”
Section: Discussionmentioning
confidence: 99%